Tingkat Adaptasi Beberapa Varietas Kedelai terhadap Naungan - Sundari, Titik; A.S., Gatut Wahyu (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
The aim of this research was to identify adaptability of 7 soybean varieties under five levels of shading. The soybean varieties tested were Tanggamus, Pangrango, Sinabung, Willis, Ijen, Lokon, and Malabar, while the five shading treatments were: no shading (N0), 15%-15% (N1), 30%-15% (N2), 45%-15% (N3), and 60%-15% (N4). The trial in each shading environment was arranged in a randomized block design with three replications. The data collected were growth variables (leaf numbers, plant heights, and stem diameters), number of filled pods, and seed yields. Data of the seed yields were analyzed using the Additive Main Effects and Multiplicative Interaction (AMMI) analysis method. Results showed that adaptability of soybean varieties to different levels of shading varied. Based on the interaction Ammi-1 biplot graph, variety Ijen was not suitable to be grown under shading environment. Varieties Sinabung and Wilis were more suitable for low level of shading environment (15%); Malabar was more suitable for moderate level of shading (45%), and Lokon was more suitable for planting under shading (60%) condition. Variety Pangrango was considered as adaptive to all levels of shading environments.